ANALISIS PSIKOLOGI SASTRA TERHADAP ASPEK KEPRIBADIAN TOKOH PADA NOVEL 7 SAYAP PENDOSA KARYA JIENARA - Elsyie Damayanti; Fera Zasrianita; Dina Putri Juni Astuti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study is motivated by the importance of novels as a medium for characters to convey messages through writing. Novels are not only a medium for reading but also contain moral messages that authors wish to convey to readers. The main issue in this study is how authors describe psychological aspects of literature as reflected in the development of characters' personalities and what psychological factors influence changes in characters' personalities in Jienara's novel 7 Sayap Pendosa (Seven Wings of Sin). This novel presents the characters' complex inner conflicts due to life experiences, trauma, and social pressure. The approach used in this study is literary psychology with a qualitative descriptive method. The research data consists of narrative quotations and character dialogues in the novel that show aspects of the characters' personalities. Data collection techniques were carried out through reading and note-taking. The results of the study show that the characters' personalities are reflected through psychological aspects such as emotions, motivations, inner conflicts, and defense mechanisms. Factors that influence the characters' personalities include Id, Ego, Superego. The novel 7 Sayap Pendosa not only presents a fictional story, but also the psychology of characters that are realistic and relevant to social life. Keyword: Literary psychology, aspects of character personality, character personality factors, the novel "7 Wings of Sinners." Abstrak: Penelitian ini dilatarbelakangi oleh pentingnya karya sastra novel sebagai media tokoh menyampaikan pesan melalui tulisan. Novel bukan hanya sebagai perantara bacaan tetapi mengandung pesan moral yang ingin disampaikan kepada pembaca. Permasalahan utama dalam penelitian ini adalah bagaimana penulis mendeskripsikan aspek psikologi sastra tercermin dalam perkembangan kepribadian tokoh dan faktor-faktor psikologi apa yang memengaruhi perubahan kepribadian tokoh didalam novel 7 sayap pendosa karya Jienara. Novel ini menyajikan konflik batin tokoh yang kompleks akibat pengalaman hidup, trauma, dan tekanan lingkungan sosial. Pendekatan yang digunakan dalam penelitian ini adalah psikologi sastra dengan metode deskriptif kualitatif. Data peneltian berupa kutipan-kutipan naratif dan dialog tokoh dalam novel yang menunjukan aspek kepribadian tokoh. Tehnik penumpulan data dilakukan melalui studi tehnik baca-catat. Hasil penelitian menunjukan bahwa kepribadian tokoh tercermin melalui aspek psikologi seperti emosi, motivasi, konflik batin dan mekanisme pertahanan diri. Faktor yang memengaruhi kepribadian tokoh meliputi faktor Id, Ego, dan Superego. Novel 7 sayap pendosa tidak hanya menghadirkan cerita fiksi, tetapi juga kejiwaan tokoh yang realitas dan relevan dengan kehidupan sosial. Kata kunci: Psikologi Sastra, Aspek Kepribadian Tokoh, Novel 7 Sayap Pendosa